COVID‐19 and food prices in sub‐Saharan Africa. (27th April 2021) - Agyei, Samuel Kwaku; Isshaq, Zangina; Frimpong, Siaw; Adam, Anokye Mohammed; Bossman, Ahmed; Asiamah, Oliver
Abstract: This study investigated the impact of the novel coronavirus disease 2019 (COVID‐19) outbreak on prices of maize, sorghum, imported rice and local rice in sub‐Saharan Africa (SSA). We estimated dynamic panel data models with controls for macroeconomic setting using general method of moments estimation. The study found that the COVID‐19 outbreak led to increases in food prices of the sampled countries. Restrictions on movements or lockdowns in the wake of COVID‐19 was associated with an increase in the price of maize only. We also found that exchange rate, inflation and crude oil prices exerted a detrimental effect on food prices. We recommend that governments of SSA countries invest in infrastructure that improves efficiencies in the food supply chain during pandemics. Providing adequate support to industries in the value chain will also improve food availability and food price stability post‐COVID‐19.